2014
DOI: 10.1371/journal.pone.0093449
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Is Augmented in Dystrophic Skeletal Muscle and Plays a Role in Decreasing Associated Fibrosis

Abstract: Duchenne muscular dystrophy (DMD) is the most common inherited neuromuscular disease and is characterized by absence of the cytoskeletal protein dystrophin, muscle wasting, and fibrosis. We previously demonstrated that systemic infusion or oral administration of angiotensin-(1-7) (Ang-(1-7)), a peptide with opposing effects to angiotensin II, normalized skeletal muscle architecture, decreased local fibrosis, and improved muscle function in mdx mice, a dystrophic model for DMD. In this study, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 53 publications
5
50
0
2
Order By: Relevance
“…Ang (1-7), mainly produced from Ang II by ACE2 and signaling through the Mas receptor, has been reported to regulate skeletal muscle insulin sensitivity (34,35), decrease fibrosis, and improve muscle function in a mouse model of muscle dystrophy (36). It has been shown by us (2-9) and by others (10 -12) (4,18), which is consistent with the fact that adult muscle fibers express little to no Ang II receptors (18,19).…”
Section: Discussionsupporting
confidence: 72%
“…Ang (1-7), mainly produced from Ang II by ACE2 and signaling through the Mas receptor, has been reported to regulate skeletal muscle insulin sensitivity (34,35), decrease fibrosis, and improve muscle function in a mouse model of muscle dystrophy (36). It has been shown by us (2-9) and by others (10 -12) (4,18), which is consistent with the fact that adult muscle fibers express little to no Ang II receptors (18,19).…”
Section: Discussionsupporting
confidence: 72%
“…Few studies have demonstrated that non-classical RAS axis is active in skeletal muscle [26,37,48,49]. Our study showed that Ang-(1-7) recovers muscle strength that was reduced by LPS.…”
Section: Discussionsupporting
confidence: 52%
“…Fibre diameter was detected by using wheat germ agglutinin (WGA) staining, which labels glycoproteins at the sarcolemma [44,45]. Briefly, freshly frozen gastrocnemius muscles were sectioned and cryosections (7 μm) were placed on glass slides, fixed in 4 % paraformaldehyde followed by incubation with AlexaFluor ® -594-conjugated WGA (Molecular Probes).…”
Section: Fibre Diameter Determination and Quantificationmentioning
confidence: 99%